Tingkat Kesehatan Bank yang Terdaftar Dalam Indeks Infobank15 Tahun 2019-2022 - Frederich, Ryozky; Syafri, Syafri (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2024)
Banks need to maintain customer trust by maintaining their performance, which can be measure through the bank’s health level. The research purpose is to show health status of banks listed on the infobank15 index from 2019 to 2022 utilizing the RGEC method. The research employs a quantitative approach through a descriptive analysis method. The sampling method uses purposive sampling, so there were six banks that became the research sample, namely “Bank Central Asia, Bank Negara Indonesia, Bank Rakyat Indonesia, Bank Pembangunan Daerah Jawa Barat dan Banten, Bank Mandiri, and Bank Pan Indonesia”. Findings of this research show that the health level of the six banks is “Very Health”, as can be seen from the average health level of each bank, although there are banks that experienced a decline in their health level in 2020.